Integrated Process For Bioconversion Of Paddy Straw, Cheese Whey And Molasses Into Ethanol (Applied Biological Research, 2020)
The present study on co-fermentation of paddy straw and cheese whey was  carried out to assess the efficacy of whey as nutritional supplement for bio ethanol production. Also, co-fermentation of paddy straw and molasses was  carried out for enhanced ethanol production to make downstream  processing and purification process easier. For agro-residues like paddy  straw, breaking of recalcitrant lignin sheath is the first and success  determining step in bioethanol production. To achieve this efficiently, five factors optimized were temperature, pressure, pH, residence time and  particle size of paddy straw. Paddy straw (particle size: 0.5 mm) immersed  in 2% sodium hydroxide solution (pH 10.0) in 1:10 was subjected to  delignification using steam collected under pressure (temperature 121°C;  pressure 15 psi) for 1 h. This resulted in 83.3% lignin removal with 86.4%  cellulose and 11.1% hemicellulose recovery. Polysaccharide rich substrate  was saccharified using commercial enzyme loadedat 7.5 FPU g-1substrate  at 50°C for 2 h. Hydrolyzed substrate was fermented with yeast strain  Candida utilis. The combined fermentation of paddy straw with cheese whey  increased ethanol production from 29.0 mL L-1to 31.0 mL L-1 without yeast  nutrient supplementation and with molasses increased to 51.0 mL L-1 ethanol with yeast nutrient supplementation.
Keywords: Bioethanol; Candida utilis; cheese whey; molasses; paddy straw